2004
DOI: 10.1002/adma.200400429
|View full text |Cite
|
Sign up to set email alerts
|

Diamond Nanorods from Carbon Nanotubes

Abstract: The synthesis of single‐crystalline diamond nanorods (with diameters of 4–8 nm and with lengths up to 200 nm) via the hydrogen plasma post‐treatment of multiwalled carbon nanotubes is described. The diamond nanorods (see Figure) are identified as having a core–sheath structure with the inner core being diamond crystal and the outer shell being composed of amorphous carbon. A growth mechanism for diamond nanorods is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 34 publications
1
59
0
2
Order By: Relevance
“…28 Density functional tight binding calculations demonstrated that formation of interlayer C-C bonds in bilayer graphene, resulting from the insertion of atomic defects, leads to a decrease in the electronic conductance of the material but also to significant electronic transport between the layers. 28 Creation of interlayer C-C bonds also has been studied in multi-walled carbon nanotubes (MWCNTs), 29 aiming at a better understanding of the initial stages of diamond nanostructure formation upon exposure of MWCNTs to a hydrogen plasma, which has been observed experimentally; [30][31] such interlayer bonds generate local nanodomains that resemble bulk diamond structures and can act as seeds for the nucleation of diamond nanocrystals embedded within the MWCNT matrix. 29 This mechanism also may be operative during the synthesis of "diamond nanotubes" (DNTs) by a process the first step of which is the formation of MWCNTs, followed by the appearance of diamond nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…28 Density functional tight binding calculations demonstrated that formation of interlayer C-C bonds in bilayer graphene, resulting from the insertion of atomic defects, leads to a decrease in the electronic conductance of the material but also to significant electronic transport between the layers. 28 Creation of interlayer C-C bonds also has been studied in multi-walled carbon nanotubes (MWCNTs), 29 aiming at a better understanding of the initial stages of diamond nanostructure formation upon exposure of MWCNTs to a hydrogen plasma, which has been observed experimentally; [30][31] such interlayer bonds generate local nanodomains that resemble bulk diamond structures and can act as seeds for the nucleation of diamond nanocrystals embedded within the MWCNT matrix. 29 This mechanism also may be operative during the synthesis of "diamond nanotubes" (DNTs) by a process the first step of which is the formation of MWCNTs, followed by the appearance of diamond nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…[267][268][269][270][271] The third route is coating a 1D materials with CNTs to form core/shell heterojunctions with CNT shells. [272][273][274][275] The fourth is directly growing though a single CVD process, and heterojunctions with CNT shells and with ZnS, [276] Mg 3 N 2 , [277] and Sn nanwire [278] cores were synthesized. The final route is based on a two-step CVD growth in an AAO template.…”
Section: Core/shell Heterojunctionsmentioning
confidence: 99%
“…3 A schematic figure showing a possible way to nanodiamond formation in the compressed interstellar cloud due to double supernova shock wave fronts following the Hansen model (Hansen et al 2007). Scale: a few hundred light years in diameter Alternatively, it is also important to note that the 2.6 nm average size of the meteoritic nanodiamonds may be related to the H-related self-terminating crystal growth process (Sun et al 2004) in the shock-wave front. On the other hand, the surface chemistry of the nanodiamonds shows a poor thermal stability between 850-1350 °C (Lu et al 2007), indicating the low-temperature crystallization process of the single diamond grains.…”
Section: (Nm)=rd (Nm/s)t (S)mentioning
confidence: 99%